Delay before drug susceptibility testing among patients with presumptive multidrug-resistant tuberculosis in Gujarat, India. (21st August 2018) - Shewade, Hemant Deepak; Shringarpure, Kalpita S; Parmar, Malik; Patel, Nikhil; Kuriya, Suraj; Shihora, Samarth; Ninama, Nittal; Gosai, Narendra; Khokhariya, Rahul; Popat, Chetan; Thanki, Hiren; Modi, Bhavesh; et al.
Abstract: Background: Reducing delay in the diagnosis of multidrug-resistant tuberculosis (MDR-TB) by performing genotypic drug susceptibility testing (DST) among eligible patients as early as possible can improve clinical presentation and treatment outcomes and reduce transmission. We aimed to determine the delay from being eligible for DST to performing DST and factors associated with the delay. Methods: This was a retrospective cohort study involving record review among presumptive MDR-TB patients who underwent genotypic DST from five selected districts in the state of Gujarat, India (2014). Specimens were couriered from the designated microscopy centres (DMCs) to two designated genotypic DST facilities located outside the districts. Results: Of 2212 patients, the median duration from eligibility to the specimen being sent, from the specimen being sent to DST and from eligibility to DST was 3, 5 and 8 d, respectively. Patients from DMCs in teaching hospitals and with presumptive MDR-TB criteria 'follow-up smear positive' and 'TB-human immunodeficiency virus co-infection' had a significantly higher risk of delay between eligibility and testing (≥8 d). The delay in the specimen being sent after eligibility contributed to high delays in these subgroups. Conclusion: The districts were doing well in implementing timely DST among presumptive MDR-TB patients. However, there is room for improvement in reducing the delays in the sending of specimens among certain patient subgroups.